Control tributario, principios constitucionales y rol de la administración tributaria - Valdivieso Ordóñez, Gabriela (2020)
The purpose of this article is to examine the powers of the Tax Administration (TA) on the basis of constitutional principles to identify cross-cutting elements such as verification, inspection, verification and investigation are integrated or not in the tax control, it is appreciated that the control of the TA is expressed in the determining - supervisory faculty and that the same denotes legality to assertively contribute to the effective payment of taxes, without exacerbating the state power. It is intended to establish that the tax control is exclusive to the determining-supervisory faculty, since from and to it the role of the TA becomes effective, moreover, the other faculties revolve around it, such as the sanctioning faculty which is instrumental to the determination and collection of tax obligations. In the same way, the tax control has as a key tool the tax audit itself that can be extended towards the fiscalization of the taxpayer's economic activity, becoming an ideal mechanism for the administrative entity, notwithstanding that this control is also exercised by the taxpayer , in order to be comptroller of the actual effect and thus mitigate internal risks.